Antenna array geometries and algorithms for direction of arrival estimation - Xiong, Hao (2013)
Direction of arrival (DOA) estimation with the antenna array was a forever topic of scientist. In this dissertation, a detailed comparison of the direction of arrival (DOA) estimation algorithms, including three classic algorithms as MUSIC, Root-MUSIC and ESPRIT, was performed and an analysis of various array geometries’ (configurations) properties in DOA estimation was demonstrated. Cramer-Rao Bound (CRB) was used for theoretic analysis and Root Mean Square Error (RMSE), which determined the best performance for a given geometry, regardless the specific estimation algorithm used, was implemented in simulation comparison.